Legal Review Analysis of the Protection of Workers' Wage Rights in the MSME Sector in Manokwari - Djaena, Oktafina; Samangun, Christina; Carina Budi Siswani (Golden Ratio of Law and Social Policy Review, 2025)
This study examines the legal protection of workers' wage rights in the Micro, Small, and Medium Enterprises (MSMEs) sector in Manokwari, which continues to face various legal and factual obstacles. Although national regulations, such as the revised Law Number 13 of 2003 concerning Manpower and Government Regulation Number 36 of 2021, have established wage standards, implementation in the field remains far from optimal. Informal employment conditions, low worker legal awareness, and limited local government oversight hinder the adequate fulfillment of wage rights. Furthermore, enforcement of legally binding court decisions also faces various substantive and procedural obstacles. This study uses a normative-empirical approach using literature study methods and qualitative analysis to examine laws and regulations, implementation practices in the field, and the role of law enforcement officials, particularly the prosecutor's office. The findings indicate that synergy between regulatory strengthening, worker empowerment, effective oversight, and the strategic role of law enforcement officials is crucial to improving the protection of MSME workers' wage rights in Manokwari. The results of this study are expected to form the basis for developing employment law enforcement policies and strategies that are more favorable to workers in the MSME sector, particularly in areas with unique socio-economic and geographical challenges.